2009
DOI: 10.1086/593690
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistically Optimistic Consumers: A Selective Hypothesis Testing Account for Optimism in Predictions of Future Behavior

Abstract: Individuals tend to make unrealistically optimistic self assessments about themselves and their future behavior. While little studied in marketing, unrealistic optimism by consumers may have negative consequences for both marketers and consumers. This dissertation proposes and explores a selective hypothesis testing view of unrealistic optimism. Specifically, I propose that consumers adopt the tentative hypothesis that they will behave in an ideal fashion when predicting their future behavior. They then select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 67 publications
(76 reference statements)
5
79
1
Order By: Relevance
“…Typical consumers are overly optimistic (Weinstein, 1980(Weinstein, , 1987(Weinstein, , 1989Tanner and Carlson, 2009) and are thus expected, in hypothetical situations, to misforecast (i.e., underestimate) the real pain of paying as well as the real badness of consuming bad food. This can be expressed as:…”
Section: Kang and Camerermentioning
confidence: 99%
See 4 more Smart Citations
“…Typical consumers are overly optimistic (Weinstein, 1980(Weinstein, , 1987(Weinstein, , 1989Tanner and Carlson, 2009) and are thus expected, in hypothetical situations, to misforecast (i.e., underestimate) the real pain of paying as well as the real badness of consuming bad food. This can be expressed as:…”
Section: Kang and Camerermentioning
confidence: 99%
“…However, many studies in behavioral economics have shown a substantial, systematic gap: typically, hypothetical valuations are greater than real valuations (Cummings et al, 1995;Johannesson et al, 1998;List and Gallet, 2001;Ariely and Wertenbroch, 2002;Little and Berrens, 2004;Murphy et al, 2005;Blumenschein et al, 2007;Tanner and Carlson, 2009). To remedy this typical upward "Yes" bias, in marketing research conjoint analysis using hypothetical preference data has been extended and improved through hybrid incentive-aligned methods in which an inferred choice will be implemented for real (Ding et al, 2005;Ding, 2007;Dong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations